Computational Chemistry as a Media in Learning Chemical Molecules Through 3D Visualization to Enhance Students' Spatial and Analytical Abilities - Muhamad Farhan Ramadhan; Leny Heliawati; Bibin Rubini (Jurnal Pemberdayaan Masyarakat, 2025)
Chemical molecules are a challenging topic for students because they are abstract and difficult to visualize. Students continue to struggle with understanding sub-microscopic concepts and lack the analytical skills necessary to solve chemical problems. Spatial and analytical abilities are essential for developing a deeper understanding of chemical molecule structures. This study aims to enhance students' spatial and analytical abilities by applying the Inquiry-Based Learning model using PyMOL as a 3D visualization medium in teaching chemical molecule structures. The method used in this study is a quasi-experiment with a pretest-posttest control group design, involving two groups of tenth-grade classes. The experimental class utilized PyMOL as a 3D visualization medium, whereas the control class employed Molymod kits. The results showed that students who learned using PyMOL experienced significant improvements in both spatial and analytical abilities. Correlation analysis showed a positive relationship between spatial and analytical abilities. Students' responses to the learning process are positive. This study demonstrates that using PyMOL as a medium for technology-based 3D visualization can make abstract concepts easier to understand and help students develop critical and systematic thinking skills.